2007
DOI: 10.1007/s11661-007-9384-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Annealing and Pressure on Devitrification and Mechanical Properties of Amorphous Al87Ni7Gd6

Abstract: Annealing studies at different temperatures, as well as those conducted with 940 MPa hydrostatic pressure, were conducted on amorphous ribbons of Al 87 Ni 7 Gd 6 . The studies were performed to investigate the evolution of structure under different conditions and to particularly examine the effects of superimposed hydrostatic pressure during annealing. This amorphous alloy devitrifies at low temperatures via the precipitation of nano-crystalline a-Al particles. The effects of these various exposures on the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Similar changes to hardness have been reported after exposure to high temperatures for other metallic glass systems. [7,16] B. Thermal Exposure Effects on Microhardness Figure 3 shows the effect of exposure time on microhardness (plotted in GPa) evolution obtained on six separate samples held at 150°C, 275°C, 300°C, 400°C, 500°C, and 562°C, respectively, for times up to 300 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…Similar changes to hardness have been reported after exposure to high temperatures for other metallic glass systems. [7,16] B. Thermal Exposure Effects on Microhardness Figure 3 shows the effect of exposure time on microhardness (plotted in GPa) evolution obtained on six separate samples held at 150°C, 275°C, 300°C, 400°C, 500°C, and 562°C, respectively, for times up to 300 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…The solute-enriched glassy matrix caused by precipitation of pure a-Al particles also may result in an increase in microhardness. The changes in solute concentration after annealing were estimated from the volume fraction of a-Al obtained according to XRD analysis in the manner previously used by Wesseling et al [16] as shown in Figure 8, assuming the rejected solute is distributed homogeneously in the amorphous matrix. The results show that the microhardness depends linearly on the solute concentration in the matrix, suggesting that the enrichment of solute is more likely the main strengthening mechanism, as proposed in previous reports, [16,17] and is consistent with the effects of the chemistry changes on the hardness changes in the amorphous ribbons, also shown in Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…There are also experimental evidence which show increase in the pressure sensitivity with increasing temperature cf. Wesseling et al (2008). 6 The values for the material parameters fs n2 ; s n3 ; f f ; n à ; k s; s à g can be more accurately determined by fitting it to the stress-strain curves along with the free volume evolution data during plastic deformation.…”
Section: Experimental Procedures and Finite-element Simulationsmentioning
confidence: 99%